Diets optimized for environmental sustainability and health: implications for diet costs across socio-economic positions for Dutch adults - Vellinga, Reina E.; Heerschop, Samantha N.; Biesbroek, Sander; van 't Veer, Pieter; Drijvers, Jose; van Bakel, Marieke; Hollander, Anne; Temme, Elisabeth H. M. (Frontiers in Nutrition, 2025)
Background:Universal access to healthy, safe, and environmentally sustainable diets is essential across all socio-economic backgrounds to improve human and planetary health.ObjectiveThis modeling study examined the transition to healthier and more environmentally sustainable diets across socio-economic groups in the Netherlands, and investigated the associated implications for diet costs.MethodsFood consumption data for 1,747 adults were derived from the Dutch National Food Consumption Survey 2019–2021. Participants were categorized according to their highest attained educational level (low, intermediate, high) as proxy for socio-economic position (SEP). For each individual, the diet was minimized for greenhouse gas (GHG) emissions and maximized for diet quality according to the Dutch Healthy Diet 2015 (DHD15) index. Optimized diets were made using a benchmark approach, involving linear combinations of current diets, either within or across the three educational subgroups. Constraints limited individual dietary changes to within 33% of current consumption, except for less commonly consumed food groups. Diet costs were compared between current and optimized diets. Secondary outcomes included nutritional aspects and additional environmental impact indicators.ResultsThe results show that modest dietary changes led to a 19%−24% reduction in GHG emissions and a 52%−56% improvement in diet quality, without increasing median diet costs across socio-economic subgroups. Depending on the educational subgroup, optimized diets included more vegetables, fruits, nuts, legumes, and fish, and less grains, dairy, meat, and sugars. More pronounced improvements were found when the optimization was not stratified by educational level.ConclusionAcross all socio-economic subgroups, modest dietary adjustments can improve health and environmental sustainability without added costs, offering a viable pathway to bridge socio-economic disparities in diet quality. Furthermore, socio-economic disparities in diet quality can be reduced without additional diet costs, provided these educational subgroups are willing and facilitated to adopt diets divergent from their peer group.